Walking on paintings: Assessment of passive haptic feedback to enhance the immersive experience - Ziat, Mounia; Jhunjhunwala , Rishi; Clepper , Gina; Kivelson , Pamela Davis; Tan , Hong Z. (Frontiers in Virtual Reality, 2022)
Virtual reality has been used in recent years for artistic expression and as a tool to engage visitors by creating immersive experiences. Most of these immersive installations incorporate visuals and sounds to enhance the user's interaction with the artistic pieces. Very few, however, involve physical or haptic interaction. This paper investigates virtual walking on paintings using passive haptics. More specifically we combined vibrations and ultrasound technology on the feet using four different configurations to evaluate users' immersion while they are virtually walking on paintings that transform into 3D landscapes. Results show that participants with higher immersive tendencies experienced the virtual walking by reporting illusory movement of their body regardless the haptic configuration used.